ROCK Inhibitor-Induced Promotion of Retinal Pigment Epithelial Cell Motility during Wound Healing - Hiroyuki Kamao; Atsushi Miki; Junichi Kiryu (Journal of Ophthalmology)
Purpose. No standard therapy for RPE tear, a complication of neovascular age-related macular degeneration, exists even though RPE tears cause severe vision loss, and promotion of cell proliferation and/or migration could be a candidate RPE tear therapy. The aim of this study is to evaluate the effect of Rho-associated coiled-coil containing kinase (ROCK) inhibitor Y27632 on retinal pigment epithelial (RPE) cell motility during wound healing. Methods. Human RPE cells were cultured in media with and without 10 μM Y27632. A luminescent cell viability assay and vinculin immunocytochemistry were used to test the Y27632 effect on RPE cell adhesion. The mean size of vinculin puncta was quantified from immunofluorescence images. RPE cell motility during wound healing was evaluated using time-lapse imaging and measuring cell migration distances and cell coverage rate in wound fields. Results. The number of adhered RPE and mean size of vinculin puncta were, respectively, 20519 cells and 3.65 μm2 under nontreatment and 23569 cells and 0.66 μm2 under Y27632 treatment. Cell migration distance and cell coverage percentage for untreated and Y27632-treated cells were 98.9 and 59.4% and 203.4 and 92.5%, respectively. Conclusions. Inhibition of ROCK signaling by using 10 μM Y27632 promoted RPE cell motility during wound healing by reducing RPE cell adhesion strength.